Saberes docentes sobre alfabetização em contexto de variedades linguísticas de português/espanhol - Salgado, Daniela Fonseca da Silva (2018)
This study investigates teachers knowledge about literacy for children speakers of Portuguese and Spanish in public elementary schools in Foz do Iguaçu. This city forms a triple border with Puerto Iguazú, in Argentina, and Ciudad del Este, in Paraguay. Foz do Iguaçu has 51 municipal schools from initial years of elementary school. We note the scarcity of specific pedagogical proposals and policies aimed at literacy in a border context We note the lack of specific pedagogical proposals and policies aimed at literacy in a frontier context. We show that, despite this, there are teachers in the early years of elementary school who recognize there are specifics in a school context with speakers of variants of the Portuguese and the variants of the Spanish language. Although in Paraguay Guarani is an official language concomitantly with Spanish, there is no similarity with the Portuguese as the Spanish language. Thus, this study focused on teaching knowledge about Portuguese / Spanish linguistic varieties, whose similarities do not necessarily affect the understanding among the interlocutors but may affect the initial appropriation process in literacy. We adopted the qualitative, dialectical, social-critical and micro-social methodology to investigate the relationships between literacy in a border context, from the particular case of a school in Foz de Iguaçu, where children from Argentina and Paraguay study. We use, as a methodological instrument, semi-structured interviews and a focus group, with the aim of understanding what the teaching knowledge is about the specificities of literacy in this context. We conclude that teachers perceive that there are specificities in literacy, but they do not know the linguistic perspective of literacy, since this is not contemplated by the continuous formation of teachers of the municipality. Among those interviewed, teachers who know Spanish have demonstrated that they have more knowledge about literacy in the frontier context where they study children who speak Portuguese and Spanish.